WELL-BEING AND WORK SPECIFICS FOR FITNESS TRAINERS IN LATVIA - Ķeizāne, Aleksandra; Čupriks, Leonīds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The work-related load can cause serious health issues and discomfort. Ligament and muscle sprains and inflammations, psycho-emotional issues, burnout, and other problems among trainers are not treated in due course and contribute to the inability to work in the future. The profession of a fitness trainer is quite challenging – heavy workload, highly changing environment, noise, the risk factors, high responsibility, high flow of people, high competition, and a relatively low salary. Every day, fitness trainers help others to improve their health and appearance. However, trainers often forget about how much the specifics of their work can harm themselves. Therefore, the purpose of this study is to investigate the work specifics of fitness trainers and how it affects the well-being of trainers in Latvia. An anonymous online survey was conducted to achieve this goal. The survey consisted of 26 closed-ended questions with multiple-choice answers and the possibility to add one’s own response option. The survey was divided into blocks, namely qualification and work experience, work specifics and conditions, rest and recovery, and characteristics of well-being. In total, 141 fitness trainers from Latvia participated in the study, of which 92 were women and 49 were men. For data analysis, the SPSS 18.0 software was used for performing mathematical and descriptive statistics. Analysing the obtained results, it can be concluded that fitness trainers in Latvia have a very heavy workload on a daily basis, there is practically no opportunity to rest and recover between the training sessions, there are very few or no days off at all, there is often no time and energy to fully and qualitatively focus on one’s own body and physical form, and often there are no regular visits to qualified specialists who could help trainers to improve their own well-being. All of this contributes to the discomfort, pain, and ill health among fitness trainers on a daily basis. Therefore, this issue needs to be addressed at the industry level.